Hydrogenation catalyst and preparation method and application thereof
By using amorphous NiWO4 materials and inorganic heat-resistant matrix as support and introducing organic matter in two steps, the shortcomings of existing hydrogenation catalysts in terms of vulcanization, activity and stability are solved, and effective treatment of high-sulfur and high-nitrogen crude oils and guaranteeing the quality of aviation coal products are achieved.
Patent Information
- Application Number
- CN202311413584.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-10-27
AI Technical Summary
The existing hydrogenation catalysts have shortcomings in vulcanization, activity and stability, and it is difficult to effectively treat impurities in high-sulfur and high-nitrogen crude oils, resulting in risks in the quality of aviation coal products.
Amorphous NiWO4 material and inorganic heat-resistant matrix are used as composite support, and different types of organic matter are introduced in two steps to improve the activity and stability of the catalyst.
The vulcanization performance and stability of the hydrogenation catalyst are significantly improved, the ability to remove sulfur impurities in aviation coal raw materials is enhanced, and the product quality and equipment operation cycle are extended.
Smart Images

Figure CN119897134A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrorefining, and in particular to a hydrogenation catalyst and a preparation method and application thereof. Background Art
[0002] As environmental regulations become increasingly stringent around the world, the demand for clean fuels is also growing. Hydroprocessing technology is an effective means of producing clean fuels. Therefore, the number of hydrogenation units in major refineries is increasing.
[0003] The demand for clean jet fuel is increasing at home and abroad. Hydrogenation can not only remove the mercaptan sulfur in the raw materials, but also deeply hydrogenate the jet fuel to improve the cleanliness of the jet fuel. The hydrogenation process of jet fuel in my country is generally a low-pressure hydrogenation process, which requires high low-temperature activity of the catalyst. The No. 3 jet fuel standard GB-6537-2018 currently implemented in my country requires that the total sulfur content is not higher than 2000μg / g, but with the continuous improvement of environmental protection requirements, the demand for more environmentally friendly low-sulfur jet fuel products will continue to increase. In the past, straight-run kerosene had a narrow distillation range and low content of impurities such as sulfur and nitrogen. High-quality jet fuel could be produced at a moderate hydrogenation depth. However, with the increase in the types of crude oil processed by refineries in recent years, the proportion of high-sulfur and high-nitrogen crude oil has increased, which has increased the content and types of impurities in jet fuel raw materials, increased the difficulty of jet fuel production, and there are certain risks in product quality, such as thermal oxidation stability and color stability. Therefore, the development of highly active jet fuel hydrogenation catalysts can better solve the problems of raw material deterioration and product index improvement, better ensure product quality, and extend the operation cycle of the device.
[0004] In order to develop catalysts with higher activity and better desulfurization effect, researchers have tried different methods to prepare different hydrogenation catalysts. Patent application CN113941351A discloses aviation kerosene hydrogenation catalysts and preparation methods thereof. By modifying the catalyst with phosphorus and / or boron, the acidity of the catalyst is increased and the mesoporous pore size is constructed, thereby improving the desulfurization ability of the catalyst. However, the introduction of acidic components will, on the one hand, aggravate carbon deposition during the reaction process, and on the other hand, cause certain cracking reactions to occur, reduce the liquid yield of the product, and have a certain impact on the aviation kerosene hydrogenation reaction process.
[0005] Patent application CN101733151A discloses a distillate oil hydrorefining catalyst. The carrier is carbonized by a solution containing an organic solvent, and the specific surface area and pore volume of the catalyst can be adjusted by changing the carbon content, thereby improving the hydrodesulfurization activity of the catalyst to a certain extent. However, during the long-term operation of the carbonized carrier, the stability of the carbon species is poor and will change to a certain extent, which poses risks and deficiencies to the stability of the catalyst.
[0006] Patent application CN104437571A discloses a hydrodesulfurization catalyst, preparation method and application thereof. The catalyst is prepared by using a carrier modified with titanium oxide-alumina to load metals, but when processing aviation kerosene or diesel raw materials with high sulfur content, the active metal of the catalyst is relatively single and the hydrogenation capacity is poor. When faced with inferior raw materials, the adaptability of the catalyst needs to be further improved. Summary of the invention
[0007] The purpose of the present invention is to overcome the problems of the prior art that hydrogenation catalysts are not easy to sulfidize, have poor activity and stability, and to provide a hydrogenation catalyst and a preparation method and application thereof. The method uses an amorphous NiWO4 material and an inorganic heat-resistant matrix as a composite carrier, introduces different types of organic matter in two steps, and improves the activity and stability of the catalyst.
[0008] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a hydrogenation catalyst, wherein the method comprises the following steps:
[0009] (1) impregnating a support with a solution containing an active metal and a quaternary ammonium salt compound, and then performing a first calcination to obtain a calcined product; the active metal is selected from at least one of the metals of Group VIII and / or at least one of the metals of Group VIB, and the support comprises an amorphous NiWO4 material and an inorganic heat-resistant matrix;
[0010] (2) post-treating the calcined product of step (1) with an organic compound, and then performing a second calcination to obtain a hydrogenation catalyst, wherein the organic compound is selected from at least one of an alcohol compound, a carboxylic acid compound and an organic amine compound.
[0011] Preferably, in step (1), based on the total amount of the calcined product, the carbon content in the calcined product is 0.5-2.5% by weight.
[0012] Preferably, the mass ratio of the organic compound in step (2) to the carbon in the calcined product in step (1) is 1:1-10:1, more preferably 2:1-8:1.
[0013] The second aspect of the present invention provides a hydrogenation catalyst prepared by the method described in the first aspect.
[0014] The third aspect of the present invention provides an application of the hydrogenation catalyst described in the second aspect in the hydrogenation reaction of aviation kerosene raw materials.
[0015] The method provided by the present invention selects amorphous NiWO4 material and an inorganic heat-resistant matrix as a composite carrier. Compared with directly loading W onto the carrier, the strong interaction between metal W and the carrier can be better eliminated, which is more conducive to the sulfurization of metal W. At the same time, metal Ni and W are connected through oxygen bridges, which is more conducive to the formation of abundant Ni-WS active centers during the sulfurization process.
[0016] The method provided by the present invention selects NiWO4 material with high activity and good diffusion channels to construct a composite carrier, and the NiWO4 material remains in an amorphous state, so that it has a large specific surface area and pore volume; at the same time, active metals are loaded on the carrier, which can further strengthen the interaction between the active metals, exert the synergistic effect between the active metals, and improve the hydrogenation activity.
[0017] The method provided by the present invention introduces different kinds of organic matter in two steps. The introduction of organic matter helps to disperse active metals and avoid aggregation of active metals. The introduction of quaternary ammonium salt compounds helps active metals to form heteropoly acid salt copolymers, enhances the synergistic effect between active metals, and helps to form more Ni-Mo-S active centers in the subsequent process. The subsequent introduction of organic compounds can further disperse the active metals and help to form more active centers. At the same time, different kinds of organic matter are introduced in two different ways and calcined to form some residual carbon on the carrier, which helps to reduce the aggregation of active metals and improve the activity and stability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is the XRD spectrum of the NiWO4 material in Example 1 of the present invention;
[0019] Figure 2 It is the XRD spectrum of the NiWO4 material in Comparative Example 6 of the present invention. DETAILED DESCRIPTION
[0020] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0021] A first aspect of the present invention provides a method for preparing a hydrogenation catalyst, wherein the method comprises the following steps:
[0022] (1) impregnating a support with a solution containing an active metal and a quaternary ammonium salt compound, and then performing a first calcination to obtain a calcined product; the active metal is selected from at least one of the metals of Group VIII and / or at least one of the metals of Group VIB, and the support comprises an amorphous NiWO4 material and an inorganic heat-resistant matrix;
[0023] (2) post-treating the calcined product of step (1) with an organic compound, and then performing a second calcination to obtain a hydrogenation catalyst, wherein the organic compound is selected from at least one of an alcohol compound, a carboxylic acid compound and an organic amine compound.
[0024] The preparation method provided by the present invention selects amorphous NiWO4 material as a part of the carrier, the amorphous NiWO4 material serves as an active center and a diffusion channel, and at the same time strengthens the interaction between active metal nickel and tungsten, thereby solving the problem of difficulty in sulfurization after the active metal tungsten interacts with the carrier; the NiWO4 material and the active alumina material are composited to prepare the carrier, so as to obtain a metal-containing catalyst carrier with a rich specific surface area, and a solution of a quaternary ammonium salt compound is loaded on the carrier, which can promote the active metal to form a heteropolyacid salt through the addition of organic matter, thereby producing a certain synergistic effect, and on the other hand, part of the active metal is loaded on the NiWO4 material, and after a subsequent sulfurization treatment, the interaction between the active metals is enhanced, thereby forming more active centers; further, different types of organic matter are simultaneously introduced in two different ways and calcined, so that part of residual carbon can be formed on the carrier, which helps to reduce the aggregation of active metals and improve the activity and stability of the catalyst.
[0025] In the present invention, there is no particular limitation on the type of active metal, and any active metal conventionally defined in the art is applicable to the present invention. Preferably, the active metal is selected from Ni and / or Mo, preferably Ni and Mo.
[0026] In the present invention, the source of the active metal can be selected in a wide range, as long as the required active metal can be provided. Preferably, the active metal is provided by a precursor of each active metal, more preferably provided by a soluble compound of each active metal, and more preferably at least one selected from nickel nitrate, nickel chloride, basic nickel carbonate and nickel sulfate, and at least one selected from ammonium molybdate, sodium molybdate and molybdenum oxide.
[0027] In the present invention, the activity and stability of the hydrogenation catalyst are improved by controlling the amount of active metal. Preferably, the amount of the active metal precursor is such that the prepared hydrogenation catalyst has a Ni content of 0.1-10% by weight in terms of oxide and a Mo content of 5-30% by weight in terms of oxide, wherein Ni is calculated as NiO and Mo is calculated as MoO3.
[0028] In the present invention, there is no particular limitation on the amount of the carrier. Preferably, the mass ratio of the Ni precursor to the amorphous NiWO4 material is 1:3-1:30 in terms of oxide.
[0029] In the present invention, preferably, the method further comprises introducing a phosphorus-containing compound in step (1), and in the present invention, the phosphorus-containing compound is introduced as an auxiliary agent to dissolve the active metal precursor (e.g., active metal precursor oxide molybdenum oxide). In the present invention, the selection range of the types of phosphorus-containing compounds is relatively wide, and the phosphorus-containing compounds conventionally defined in the art are applicable to the present invention. Preferably, the phosphorus-containing compound is selected from at least one of phosphoric acid, orthophosphate, metaphosphate, hypophosphite, hydrogen phosphate, dihydrogen phosphate and hydrocarbon phosphonic acid. In the present invention, there is no particular limitation on the amount of the phosphorus-containing compound, as long as it can dissolve the active metal precursor. Preferably, the molar ratio of the Mo precursor to the phosphorus-containing compound is 1:1-5:1, calculated as oxide.
[0030] In the present invention, by introducing quaternary ammonium salt compounds, active metals are helped to form heteropolyacid salt copolymers, the synergistic effect between active metals is enhanced, and the formation of active centers is more helped. The present invention is not particularly limited to the specific type of quaternary ammonium salt compounds, and the quaternary ammonium salt compounds conventionally defined in this area are all applicable to the present invention. Preferably, in step (1), the quaternary ammonium salt compounds are selected from quaternary ammonium salt compounds of C4-C20, preferably selected from at least one of tetramethyl ammonium bromide, tetraethyl ammonium bromide, tetrapropyl ammonium bromide, tetrabutyl ammonium bromide, dodecyl trimethyl ammonium bromide and hexadecyl trimethyl ammonium bromide, more preferably at least one of tetrabutyl ammonium bromide, dodecyl trimethyl ammonium bromide and hexadecyl trimethyl ammonium bromide.
[0031] In the present invention, the activity and stability of the hydrogenation catalyst are improved by regulating the dosage of the quaternary ammonium salt compound and the active metal to enhance the synergistic effect between the active metals. Preferably, in step (1), the molar ratio of the quaternary ammonium salt compound to the active metal Ni in terms of element is 0.3:1-3:1, and more preferably 0.5:1-2:1.
[0032] In the present invention, there is no particular limitation on the impregnation method of the active metal and the quaternary ammonium salt compound, for example, the carrier can be impregnated by a pore saturation impregnation method. According to a specific embodiment of the present invention, a metal impregnation solution of a certain volume is prepared according to the water absorption rate and mass of the carrier, and the metal impregnation solution is poured into the carrier three times and fully stirred to obtain a catalyst after pore saturation impregnation, and then dried.
[0033] In the present invention, the amorphous NiWO4 material has a smaller average grain size, which can improve the sulfurization performance of the hydrogenation catalyst. Preferably, in step (1), the average grain size of the amorphous NiWO4 material is 2-5 nm.
[0034] In the present invention, the average grain size of the amorphous NiWO4 material refers to the average size of the grains formed by the aggregation of the NiWO4 material during the synthesis process.
[0035] In the present invention, the average grain size of the amorphous NiWO4 material is measured by a high-resolution transmission electron microscopy analysis (HRTEM) method. The specific test conditions are: a Tecnai G2 F20 S-TWIN high-resolution transmission electron microscope (HRTEM) produced by FEI Company is used to characterize the sample, an accelerating voltage of 200 kV is used, the size of the grains in the sample is observed, and for the sample to be statistically analyzed, 30-50 photos are taken, the size of the grains in the photos is statistically analyzed, and the average is calculated.
[0036] In the present invention, the metal composition of the amorphous NiWO4 material is determined by elemental analysis, and the specific test conditions are: using an X-ray fluorescence spectrometer from Rigaku Corporation, quantitatively analyzing the element content by an external standard method, pressing the powder sample into tablets, and using a laser voltage of 50 kV and a laser current of 50 mA.
[0037] In the present invention, the crystal structure of the amorphous NiWO4 material is measured by the XRD method, and the specific test conditions are: using a Bruker D5005 diffractometer to characterize the sample by XRD, Cu Kα rays (λ=0.154nm), tube voltage 40kV, tube current 30mA, scanning range 5°-70°, step 0.013°, 1 step per second, and using a JCPDS-based method to analyze and determine the phase composition of the sample.
[0038] In the present invention, the amorphous NiWO4 material is in an amorphous crystalline state. It should be noted that Figure 1 It can be seen that amorphous means that the NiWO4 material will not show obvious diffraction peaks in the XRD characterization spectrum, and there is no clear crystal structure. XRF can be used to analyze the metal composition and element ratio of the material, determine its possible structural formula, and combine the weak XRD diffraction peaks to determine its amorphous structure.
[0039] In the present invention, the amorphous NiWO4 material maintains an amorphous crystal state, so that it has a large specific surface area and pore volume. It is used as part of the carrier to prepare a hydrogenation catalyst, which can improve the hydrogenation activity. Preferably, the specific surface area of the amorphous NiWO4 material is 200-300m 2 / g, and the pore volume is 0.5-1mL / g.
[0040] In the present invention, the specific surface area and pore volume of the amorphous NiWO4 material are measured by N2 physical adsorption-desorption analysis (BET) method, and the specific test conditions are: using N2 constant temperature adsorption-desorption and calculating the specific surface area and pore volume of the sample by conventional BET and BJH methods. Before analysis, the sample is dried at 120°C for 3h and then dehydrated and degassed at 300°C.
[0041] In the present invention, there is no particular limitation on the source of the amorphous NiWO4 material, for example, it can be obtained commercially, or it can be prepared by a method conventionally defined in the art. Preferably, in step (1), the amorphous NiWO4 material is prepared by the following method: a NiWO4 precursor is prepared by a solid phase reaction method and / or a precipitation method, and then subjected to a hydrothermal treatment to obtain an amorphous NiWO4 material, wherein the conditions of the hydrothermal treatment include: a temperature of 120-240°C and a time of 2-48h. Preferably, the conditions of the hydrothermal treatment include: a temperature of 140-220°C and a time of 12-36h.
[0042] In the present invention, there is no particular limitation on the preparation method of the NiWO4 precursor. For example, the precursor may be prepared by a conventional preparation method in the art, such as a solid phase reaction method or a precipitation method.
[0043] The present invention does not particularly limit the specific operation mode and conditions of the solid phase reaction method. According to a specific embodiment of the present invention, the solid phase reaction method includes: mixing the Ni metal precursor and the W metal precursor and then performing a first heat treatment. The present invention has a wide range of selection conditions for the first heat treatment. Preferably, the conditions for the first heat treatment include: a temperature of 120-200°C and a time of 12-48 hours.
[0044] The present invention does not particularly limit the specific operation mode and conditions of the precipitation method. According to another specific embodiment of the present invention, the precipitation method includes: dissolving the Ni metal precursor and the W metal precursor respectively with a solvent (preferably water) to obtain a Ni-containing metal precursor solution and a W-containing metal precursor solution, and then mixing the W-containing metal precursor solution and the Ni-containing metal precursor solution for a second heat treatment. The present invention has a wide range of conditions for the second heat treatment. Preferably, the conditions for the second heat treatment include: a temperature of 50-100°C. In the present invention, the second heat treatment is carried out under stirring conditions. The present invention does not particularly limit the conditions for the second stirring, and those skilled in the art can select according to actual conditions. The present invention does not particularly limit the amount of solvent used, and those skilled in the art can select according to actual conditions.
[0045] In the present invention, there is no particular limitation on the type of Ni precursor, as long as it can provide the Ni element. Preferably, the Ni metal precursor is a soluble Ni compound, and more preferably is at least one selected from nickel nitrate, nickel chloride, basic nickel carbonate and nickel sulfate.
[0046] In the present invention, there is no particular limitation on the type of W precursor, as long as it can provide the W element. Preferably, the W metal precursor is a soluble compound of W, and more preferably at least one selected from ammonium metatungstate, sodium tungstate and ammonium tungstate.
[0047] In the present invention, there is no particular limitation on the amount of the Ni metal precursor and the W metal precursor. Preferably, the molar ratio of the Ni-containing metal precursor to the W-containing metal precursor is 1:5-5:1, calculated on an element basis.
[0048] In the present invention, the inorganic heat-resistant matrix has a wide range of choices. Preferably, the inorganic heat-resistant matrix is selected from at least one of aluminum oxide, zirconium oxide, oxidized state, and silicon oxide, preferably aluminum oxide.
[0049] In the present invention, there is no particular limitation on the preparation method of the carrier. Preferably, the amorphous NiWO4 material and the inorganic heat-resistant matrix are molded. The present invention does not particularly limit the molding method, for example, it can be forced mechanical mixing. In the present invention, there is no particular limitation on the amount of the amorphous NiWO4 material and the inorganic heat-resistant matrix, as long as the carrier can be prepared. Preferably, the mass ratio of the amorphous NiWO4 material to the inorganic heat-resistant matrix is 1:2-1:20.
[0050] In the present invention, preferably, the method further comprises step (1) of performing a first drying treatment before the first roasting. In the present invention, the conditions for the first drying are selected in a wide range, preferably, the conditions for the first drying include: a temperature of 60-200°C, preferably 80-150°C, a time of 1-8 hours, preferably 2-6 hours, and a pressure of 0.01-0.1MPa, preferably 0.05-0.1MPa. In the present invention, preferably, the first drying is performed in an air atmosphere.
[0051] In the present invention, by regulating the carbon content in the calcined product of step (1), a portion of residual carbon is formed on the carrier, which helps to reduce the aggregation of active metals and improve the activity and stability of the catalyst. Preferably, in step (1), based on the total amount of the calcined product, the carbon content in the calcined product is 0.5-2.5% by weight, preferably 0.8-2% by weight.
[0052] In the present invention, the carbon content is measured by an infrared absorption method. The specific test conditions are: the carbon content in the sample is measured using EMIA-920V from HORIBA Company, the sample and the flux are placed in a high-frequency induction furnace for oxygen combustion, and the generated CO2 gas flows through an infrared absorption cell to absorb infrared energy, and the carbon content can be obtained from the change in energy.
[0053] In the present invention, low-temperature roasting is adopted to avoid excessive interaction between active metal and carrier caused by high-temperature roasting, which is helpful for subsequent sulfidation of active metal; at the same time, metal salt is completely decomposed in the low-temperature roasting stage to form corresponding metal oxide, and quaternary ammonium salt compound is partially decomposed, retaining a certain proportion of carbon species to modify the carrier, and cooperate with subsequent organic compounds to improve the activity of the catalyst. Preferably, in step (1), the conditions of the first roasting include: temperature of 180-350°C, time of 1-8h; further preferably, in step (1), the conditions of the first roasting include: temperature of 230-300°C, time of 2-6h.
[0054] In the present invention, preferably, the first calcination is carried out in an air atmosphere. In the present invention, the advantage of carrying out the first calcination in an air atmosphere is that the use of air atmosphere calcination can effectively convert the active metal from the form of metal salt to the form of oxide species, and at the same time partially oxidize and decompose the organic matter, effectively controlling the carbon content.
[0055] In the present invention, preferably, the pressure of the first calcination is 0.1-0.5 MPa.
[0056] In the present invention, there is no particular limitation on the type of alcohol compound. Preferably, in step (2), the alcohol compound is selected from at least one of ethylene glycol, glycerol, diethylene glycol and butanediol.
[0057] In the present invention, there is no particular limitation on the type of carboxylic acid compound. Preferably, in step (2), the carboxylic acid compound is selected from at least one of citric acid, acetic acid, oxalic acid, aminotriacetic acid, 1,2-cyclohexanediaminetetraacetic acid, aminotriacetic acid, malic acid and maleic acid.
[0058] In the present invention, there is no particular limitation on the type of organic amine compound. Preferably, in step (2), the organic amine compound is ethylenediamine and / or ethylenediaminetetraacetic acid.
[0059] In the present invention, preferably, in step (2), the post-treatment comprises: impregnating the calcined product of step (1) with a solution containing at least one of an alcohol compound, a carboxylic acid compound and an organic amine compound by an impregnation method. In the present invention, there is no particular limitation on the impregnation method of the organic compound, for example, the carrier can be impregnated by a pore saturation impregnation method. According to a specific embodiment of the present invention, according to the water absorption rate and mass of the calcined product, a corresponding volume of organic impregnation solution is prepared, the organic impregnation solution is poured into the carrier three times and fully stirred to obtain a catalyst after pore saturation impregnation, and then a drying treatment is performed.
[0060] In the present invention, the carbon content on the carrier is regulated by introducing organic matter step by step, which helps to reduce the aggregation of active metals and improve the activity and stability of the catalyst. Preferably, the mass ratio of the organic compound in step (2) to the carbon in the calcined product in step (1) is 1:1-10:1, and more preferably 2:1-8:1.
[0061] In the present invention, preferably, the method further comprises step (2) of performing a second drying treatment before the second roasting. In the present invention, the conditions for the first drying are selected in a wide range, preferably, the conditions for the second drying include: a temperature of 60-200°C, preferably 80-150°C, a time of 1-8 hours, preferably 2-6 hours, and a pressure of 0.01-0.1MPa, preferably 0.05-0.1MPa. In the present invention, preferably, the second drying is performed in an air atmosphere.
[0062] In the present invention, the second calcination is carried out at a low temperature, which helps to further disperse the active metal, form more active centers, and improve the activity and stability of the catalyst. Preferably, in step (2), the conditions of the second calcination include: a temperature of 180-350°C and a time of 1-8h; further preferably, in step (2), the conditions of the second calcination include: a temperature of 200-280°C and a time of 2-6h.
[0063] In the present invention, preferably, the pressure of the second calcination is 0.1-0.5 MPa.
[0064] In the present invention, preferably, in step (2), the second calcination is carried out under an inert atmosphere, and preferably the inert atmosphere is selected from at least one of nitrogen, helium and argon. In the present invention, the advantage of the second calcination being carried out under an inert atmosphere is that the calcination treatment is carried out in an inert atmosphere, which effectively controls the degree of decomposition of organic matter and adjusts the carbon content on the catalyst.
[0065] The second aspect of the present invention provides a hydrogenation catalyst prepared by the method described in the first aspect.
[0066] The third aspect of the present invention provides an application of the hydrogenation catalyst described in the second aspect in the hydrogenation reaction of aviation kerosene raw materials.
[0067] The hydrogenation catalyst provided by the present invention has significant advantages in diffusion channels and hydrogenation activity, and has good performance in the hydrogenation desulfurization of aviation kerosene raw materials.
[0068] In the present invention, there is no particular limitation on the type and content of each component in the aviation kerosene raw material, and the aviation kerosene raw materials conventionally defined in the art are applicable to the present invention.
[0069] The method provided by the present invention can effectively remove sulfur impurities, especially mercaptan impurities, from aviation kerosene raw materials at a relatively low temperature.
[0070] In the present invention, the conditions for the hydrogenation reaction are selected in a wide range. Preferably, the conditions for the hydrogenation reaction include: a reaction temperature of 230-300°C, a reaction pressure of 1-4 MPa, and a volume space velocity of 2-6 h -1 , hydrogen-oil volume ratio 50:1-200:1.
[0071] In the present invention, preferably, the hydrogenation catalyst is subjected to a sulfurization treatment before the reaction. In the present invention, the sulfurization treatment method is not particularly limited, as long as the active metal on the catalyst can be converted from an oxidized state to a sulfurized state. For example, the sulfurization method can be dry sulfurization or wet sulfurization. The present invention does not particularly limit the selection of sulfurization conditions, and those skilled in the art can select according to actual needs.
[0072] The present invention will be described in detail by way of examples. In the following examples, all products are commercially available unless otherwise specified.
[0073] In order to illustrate the characteristics of the present invention, the examples and comparative examples are all made of the same batch of industrially produced commercial alumina powder, which is produced by the Changling Branch of Sinopec Catalyst Co., Ltd. and has a brand name of RPB-90.
[0074] In the present invention, the carbon content is measured by infrared absorption method.
[0075] In the present invention, the average grain size of the amorphous NiWO4 material is measured by a high-resolution transmission electron microscopy (HRTEM) method.
[0076] The crystal structure of amorphous NiWO4 material was measured by XRD method.
[0077] The specific surface area and pore volume of amorphous NiWO4 materials were measured by N2 physical adsorption-desorption analysis (BET) method.
[0078] Example 1
[0079] (1) Take 24g of nickel chloride hexahydrate and 33g of sodium tungstate dihydrate, dissolve them in deionized water respectively, heat the sodium tungstate solution to 60°C, add the nickel chloride solution dropwise to form a suspension solution, transfer the suspension solution to a hydrothermal kettle for hydrothermal treatment at a temperature of 180°C for 24 hours, and obtain an amorphous NiWO4 material for standby use. The XRD spectrum is as follows Figure 1 As shown, from Figure 1 It can be seen that no obvious diffraction peak is formed, indicating that no obvious crystal structure is formed and the NiWO4 material remains in an amorphous state;
[0080] (2) 20 g of the prepared NiWO4 material and 100 g of commercial alumina powder were uniformly mechanically mixed and formed as a composite carrier;
[0081] (3) Take 120g of the above composite support, weigh 7g of basic nickel carbonate, 22g of molybdenum oxide, 6g of 85% by mass phosphate and 13g of tetrabutylammonium bromide, heat and stir to dissolve in deionized water, adjust the volume according to the saturated water absorption rate of the composite support, and use the solution to impregnate the composite support for 2 hours, the air atmosphere pressure is 0.1MPa, dry at 120°C for 4 hours, and then heat to 280°C and low-temperature roast for 4 hours at a pressure of 0.15MPa to obtain a catalyst sample M loaded with active metals, and its carbon content is 1.52%;
[0082] (4) Weigh 12.16 g of citric acid, stir and dissolve it with deionized water, and adjust the volume according to the saturated water absorption rate of sample M. Use the solution to impregnate the catalyst sample M loaded with active metal for 2 hours. The air atmosphere pressure is 0.1 MPa. After drying at 120°C for 4 hours, switch to nitrogen and heat to 265°C for low-temperature calcination for 4 hours at a pressure of 0.15 MPa to obtain catalyst C1.
[0083] The catalyst is subjected to a presulfurization treatment before use. The presulfurization treatment conditions include: in an atmosphere of 1 volume % H2S and 99 volume % H2, the catalyst is subjected to a programmed temperature-raising sulfidation treatment. The temperature raising program is from 20°C to 300°C at a rate of 1°C / min, and the temperature is kept constant for 3 hours. The ratio of the gas volume flow rate per hour to the volume of the catalyst is 200.
[0084] The hydrodesulfurization activity of the catalyst was evaluated in a 20 mL fixed bed reactor. The process conditions were as follows: inlet temperatures were 240 °C, 260 °C, and 280 °C, reaction pressure was 1.6 MPa, hydrogen-to-oil volume ratio was 60, and volume space velocity was 4 h -1 , take samples after stabilization for 24 hours, analyze the sulfur content of the product, and calculate the desulfurization rate through the difference between the sulfur content of the product and the raw material. The higher the desulfurization rate, the better the activity of the catalyst.
[0085] N2 isothermal adsorption-desorption was used and the conventional BET and BJH methods were used to calculate the specific surface area and pore volume of the catalyst. X-ray photoelectron spectroscopy was used for XPS to characterize the degree of sulfidation of the active metals of the catalyst after sulfidation. The larger the specific surface area of the catalyst, the larger the pore volume, indicating that it has more abundant diffusion channels. The catalyst after sulfidation has a higher degree of sulfidation, indicating that the utilization rate of the active metals of the catalyst is higher and there are relatively more active centers.
[0086] The properties of the raw materials are shown in Table 1, the analysis of the amorphous NiWO4 material is shown in Table 2, the results of the catalyst analysis and characterization are shown in Table 3, and the evaluation results data are shown in Table 4.
[0087] Example 2
[0088] (1) 22 g of nickel chloride hexahydrate and 38 g of sodium tungstate dihydrate were taken and dissolved in deionized water respectively. After the sodium tungstate solution was heated to 70° C., the nickel chloride solution was added dropwise to form a suspension solution. The suspension solution was transferred to a hydrothermal kettle for hydrothermal treatment under the conditions of 160° C. for 36 hours. After the hydrothermal treatment, an amorphous NiWO4 material was obtained for standby use. The NiWO4 material in Example 2 had the same amorphous state as that in Example 1.
[0089] (2) 20 g of the prepared NiWO4 material and 100 g of commercial alumina powder were uniformly mechanically mixed and formed as a composite carrier;
[0090] (3) Take 120g of the above composite support, weigh 7g of basic nickel carbonate, 22g of molybdenum oxide, 6g of 85% by mass phosphate and 13g of tetrabutylammonium bromide, heat and stir to dissolve in deionized water, adjust the volume according to the saturated water absorption rate of the composite support, impregnate the composite support with the solution for 2 hours, the air atmosphere pressure is 0.1MPa, dry at 120°C for 4 hours, heat to 280°C and calcine at low temperature for 4 hours at a pressure of 0.15MPa to obtain a catalyst sample M loaded with active metals, and its carbon content is 1.48%;
[0091] (4) Weigh 11.84 g of citric acid, stir and dissolve it with deionized water, and adjust the volume according to the saturated water absorption rate of sample M. Use the solution to impregnate the catalyst sample M loaded with active metal for 2 hours. The air atmosphere pressure is 0.1 MPa. After drying at 120°C for 4 hours, switch to nitrogen and heat to 265°C for low-temperature calcination for 4 hours at a pressure of 0.15 MPa to obtain catalyst C2.
[0092] The evaluation conditions of the catalyst are the same as those in Example 1. The analysis of amorphous NiWO4 material is shown in Table 2, the catalyst analysis and characterization results are shown in Table 3, and the evaluation result data are shown in Table 4.
[0093] Example 3
[0094] (1) 26 g of nickel nitrate and 23 g of ammonium metatungstate were mixed and ground into powder and then subjected to heat treatment at a temperature of 180° C. for 24 hours, and then transferred to a hydrothermal kettle for hydrothermal treatment at a temperature of 180° C. for 24 hours. After the hydrothermal treatment, an amorphous NiWO4 material was obtained for standby use. The NiWO4 material of Example 3 had the same amorphous state as that of Example 1;
[0095] (2) 20 g of the prepared NiWO4 material and 100 g of commercial alumina powder were uniformly mechanically mixed and formed as a composite carrier;
[0096] (3) Take 120g of the above composite support, weigh 7g of basic nickel carbonate, 22g of molybdenum oxide, 6g of 85% by mass phosphate and 13g of tetrabutylammonium bromide, heat and stir to dissolve in deionized water, adjust the volume according to the saturated water absorption rate of the composite support, and use the solution to impregnate the composite support for 2 hours, the air atmosphere pressure is 0.1MPa, dry at 120°C for 4 hours, and then heat to 280°C and low-temperature roast for 4 hours at a pressure of 0.15MPa to obtain a catalyst sample M loaded with active metals, and its carbon content is 1.51%;
[0097] (4) Weigh 12.08 g of citric acid, stir and dissolve it with deionized water, and adjust the volume according to the saturated water absorption rate of sample M. Use the solution to impregnate the catalyst sample M loaded with active metal for 2 hours. The air atmosphere pressure is 0.1 MPa. After drying at 120°C for 4 hours, switch to nitrogen and heat to 265°C for low-temperature calcination for 4 hours at a pressure of 0.15 MPa to obtain catalyst C3.
[0098] The evaluation conditions of the catalyst are the same as those in Example 1. The analysis of amorphous NiWO4 material is shown in Table 2, the catalyst analysis and characterization results are shown in Table 3, and the evaluation result data are shown in Table 4.
[0099] Example 4
[0100] (1) Take 24g of nickel chloride hexahydrate and 33g of sodium tungstate dihydrate, dissolve them in deionized water respectively, heat the sodium tungstate solution to 60°C, add the nickel chloride solution dropwise to form a suspension solution, transfer the suspension solution to a hydrothermal kettle for hydrothermal treatment, the hydrothermal conditions are temperature 180°C, time 24 hours, and obtain an amorphous NiWO4 material for standby use. The NiWO4 material in Example 4 has the same amorphous state as that in Example 1;
[0101] (2) 15 g of the prepared NiWO4 material and 100 g of commercial alumina powder were uniformly mechanically mixed and formed as a composite carrier;
[0102] (3) Take 115g of the above composite support, weigh 9g of basic nickel carbonate, 26g of molybdenum oxide, 7g of 85% phosphoric acid and 16g of tetrabutylammonium bromide, heat and stir to dissolve in deionized water, adjust the volume according to the saturated water absorption rate of the composite support, and use the solution to impregnate the composite support for 2 hours, the air atmosphere pressure is 0.1MPa, dry at 120°C for 4 hours, and then heat to 280°C and low-temperature roast for 4 hours at a pressure of 0.15MPa to obtain a catalyst sample M loaded with active metals, and its carbon content is 1.60%;
[0103] (4) Weigh 9.6 g of citric acid, stir and dissolve it with deionized water, and adjust the volume according to the saturated water absorption rate of sample M. Use the solution to impregnate the catalyst sample M loaded with active metal for 2 hours. The air atmosphere pressure is 0.1 MPa. After drying at 120°C for 4 hours, switch to nitrogen and heat to 265°C for low-temperature calcination for 4 hours at a pressure of 0.15 MPa to obtain catalyst C4.
[0104] The evaluation conditions of the catalyst are the same as those in Example 1. The analysis of amorphous NiWO4 material is shown in Table 2, the catalyst analysis and characterization results are shown in Table 3, and the evaluation result data are shown in Table 4.
[0105] Example 5
[0106] (1) Take 24g of nickel chloride hexahydrate and 33g of sodium tungstate dihydrate, dissolve them in deionized water respectively, heat the sodium tungstate solution to 60°C, add the nickel chloride solution dropwise to form a suspension solution, transfer the suspension solution to a hydrothermal kettle for hydrothermal treatment, the hydrothermal conditions are temperature 180°C, time 24 hours, and obtain an amorphous NiWO4 material for standby use. The NiWO4 material in Example 5 has the same amorphous state as that in Example 1;
[0107] (2) 20 g of the prepared NiWO4 material and 100 g of commercial alumina powder were uniformly mechanically mixed and formed as a composite carrier;
[0108] (3) Take 120g of the above composite support, weigh 7g of basic nickel carbonate, 22g of molybdenum oxide, 6g of 85% phosphoric acid and 19g of dodecyltrimethylammonium bromide, heat and stir to dissolve in deionized water, adjust the volume according to the saturated water absorption rate of the composite support, impregnate the composite support with the solution for 2 hours, the air atmosphere pressure is 0.1MPa, dry at 120°C for 4 hours, heat to 280°C and calcine at low temperature for 4 hours at a pressure of 0.15MPa to obtain a catalyst sample M loaded with active metals, and its carbon content is 1.86%;
[0109] (4) Weigh 13.02 g of propylene glycol, stir and dissolve it with deionized water, and adjust the volume according to the saturated water absorption rate of sample M. Use the solution to impregnate the catalyst sample M loaded with active metal for 2 hours. The air atmosphere pressure is 0.1 MPa. After drying at 120°C for 4 hours, switch to nitrogen and heat to 265°C for low-temperature calcination for 4 hours at a pressure of 0.15 MPa to obtain catalyst C5.
[0110] The evaluation conditions of the catalyst are the same as those in Example 1. The analysis of amorphous NiWO4 material is shown in Table 2, the catalyst analysis and characterization results are shown in Table 3, and the evaluation result data are shown in Table 4.
[0111] Example 6
[0112] (1) Take 24g of nickel chloride hexahydrate and 33g of sodium tungstate dihydrate, dissolve them in deionized water respectively, heat the sodium tungstate solution to 60°C, add the nickel chloride solution dropwise to form a suspension solution, transfer the suspension solution to a hydrothermal kettle for hydrothermal treatment, the hydrothermal conditions are temperature 180°C, time 24 hours, and obtain an amorphous NiWO4 material for standby use. The NiWO4 material in Example 6 has the same amorphous state as that in Example 1;
[0113] (2) 20 g of the prepared NiWO4 material and 100 g of commercial alumina powder were uniformly mechanically mixed and formed as a composite carrier;
[0114] (3) Take 120g of the above composite support, weigh 7g of basic nickel carbonate, 22g of molybdenum oxide, 6g of 85% by mass phosphate and 13g of tetrabutylammonium bromide, heat and stir to dissolve in deionized water, adjust the volume according to the saturated water absorption rate of the composite support, impregnate the composite support with the solution for 2 hours, the air atmosphere pressure is 0.1MPa, dry at 120°C for 4 hours, heat to 300°C and low-temperature roast for 3 hours at a pressure of 0.15MPa, and obtain a catalyst sample M loaded with active metals, and its carbon content is 1.22%;
[0115] (4) Weigh 12.2 g of citric acid, stir and dissolve it with deionized water, and adjust the volume according to the saturated water absorption rate of sample M. Use the solution to impregnate the catalyst sample M loaded with active metal for 2 hours. The air atmosphere pressure is 0.1 MPa. After drying at 150°C for 3 hours, switch to nitrogen and raise the temperature to 255°C for low-temperature calcination for 6 hours at a pressure of 0.1 MPa to obtain catalyst C6.
[0116] The evaluation conditions of the catalyst are the same as those in Example 1. The analysis of amorphous NiWO4 material is shown in Table 2, the catalyst analysis and characterization results are shown in Table 3, and the evaluation result data are shown in Table 4.
[0117] Example 7
[0118] (1) Take 24g of nickel chloride hexahydrate and 33g of sodium tungstate dihydrate, dissolve them respectively in deionized water, heat the sodium tungstate solution to 60°C, add the nickel chloride solution dropwise to form a suspension solution, transfer the suspension solution to a hydrothermal kettle for hydrothermal treatment, the hydrothermal conditions are temperature 180°C, time 24 hours, and obtain an amorphous NiWO4 material after hydrothermal treatment for standby use. The NiWO4 material in Example 7 has the same amorphous state as that in Example 1;
[0119] (2) 20 g of the prepared NiWO4 material and 100 g of commercial alumina powder were uniformly mechanically mixed and formed as a composite carrier;
[0120] (3) Take 120g of the above composite support, weigh 8g of basic nickel carbonate, 21g of molybdenum oxide, 6g of 85% by mass phosphoric acid and 14g of cetyltrimethylammonium bromide, heat and stir to dissolve in deionized water, adjust the volume according to the saturated water absorption rate of the composite support, and use the solution to impregnate the composite support for 2 hours, the air atmosphere pressure is 0.1MPa, dry at 120°C for 4 hours, and then heat to 230°C and low-temperature roast for 4 hours at a pressure of 0.15MPa to obtain a catalyst sample M loaded with active metals, and its carbon content is 1.92%;
[0121] (4) Weigh 9.6 g of citric acid, stir and dissolve it with deionized water, and adjust the volume according to the saturated water absorption rate of sample M. Use the solution to impregnate the catalyst sample M loaded with active metal for 2 hours. The air atmosphere pressure is 0.1 MPa. After drying at 120°C for 4 hours, switch to nitrogen and heat to 210°C for low-temperature calcination for 4 hours at a pressure of 0.15 MPa to obtain catalyst C7.
[0122] The evaluation conditions of the catalyst are the same as those in Example 1. The analysis of amorphous NiWO4 material is shown in Table 2, the catalyst analysis and characterization results are shown in Table 3, and the evaluation result data are shown in Table 4.
[0123] Example 8
[0124] (1) Take 24g of nickel chloride hexahydrate and 33g of sodium tungstate dihydrate, dissolve them in deionized water respectively, heat the sodium tungstate solution to 60°C, add the nickel chloride solution dropwise to form a suspension solution, transfer the suspension solution to a hydrothermal kettle for hydrothermal treatment, the hydrothermal conditions are temperature 180°C, time 24 hours, and obtain an amorphous NiWO4 material for standby use. The NiWO4 material in Example 8 has the same amorphous state as that in Example 1;
[0125] (2) 20 g of the prepared NiWO4 material and 100 g of commercial alumina powder were uniformly mechanically mixed and formed as a composite carrier;
[0126] (3) Take 120g of the above composite support, weigh 7g of basic nickel carbonate, 22g of molybdenum oxide, 6g of 85% by mass phosphate and 13g of tetrabutylammonium bromide, heat and stir to dissolve in deionized water, adjust the volume according to the saturated water absorption rate of the composite support, impregnate the composite support with the solution for 2 hours, the air atmosphere pressure is 0.1MPa, dry at 120°C for 4 hours, heat to 190°C and calcine at low temperature for 4 hours at a pressure of 0.15MPa to obtain a catalyst sample M loaded with active metals, and its carbon content is 2.10%;
[0127] (4) Weigh 16.8 g of citric acid, stir and dissolve it with deionized water, and adjust the volume according to the saturated water absorption rate of sample M. Use the solution to impregnate the catalyst sample M loaded with active metal for 2 hours. The air atmosphere pressure is 0.1 MPa. After drying at 120°C for 4 hours, switch to nitrogen and heat to 320°C for low-temperature calcination for 4 hours at a pressure of 0.15 MPa to obtain catalyst C8.
[0128] The evaluation conditions of the catalyst are the same as those in Example 1. The analysis of amorphous NiWO4 material is shown in Table 2, the catalyst analysis and characterization results are shown in Table 3, and the evaluation result data are shown in Table 4.
[0129] Comparative Example 1
[0130] (1) 100 g of commercial alumina powder was molded as a carrier, 7 g of basic nickel carbonate, 22 g of molybdenum oxide, 6 g of 85% by mass phosphoric acid and 13 g of tetrabutylammonium bromide were weighed, heated and stirred to dissolve in deionized water, the volume was fixed according to the saturated water absorption rate of the carrier, the carrier was impregnated with the solution for 2 hours, the air atmosphere pressure was 0.1 MPa, and after drying at 120° C. for 4 hours, the temperature was raised to 280° C. and low-temperature calcined for 4 hours at a pressure of 0.15 MPa to obtain a catalyst sample M loaded with active metals, and its carbon content was measured to be 1.50%;
[0131] (2) Weigh 12 g of citric acid, stir and dissolve it with deionized water, and adjust the volume according to the saturated water absorption rate of sample M. Use the solution to impregnate the catalyst sample M loaded with active metal for 2 hours. The air atmosphere pressure is 0.1 MPa. After drying at 120°C for 4 hours, switch to nitrogen and heat to 265°C for low-temperature calcination for 4 hours at a pressure of 0.15 MPa to obtain catalyst D1.
[0132] The evaluation conditions of the catalyst are the same as those in Example 1. The NiWO4 material analysis is shown in Table 2, the catalyst analysis and characterization results are shown in Table 3, and the evaluation result data are shown in Table 4.
[0133] Comparative Example 2
[0134] (1) Take 24g of nickel chloride hexahydrate and 33g of sodium tungstate dihydrate, dissolve them in deionized water respectively, heat the sodium tungstate solution to 60°C, add the nickel chloride solution dropwise to form a suspension solution, transfer the suspension solution to a hydrothermal kettle for hydrothermal treatment, the hydrothermal conditions are temperature 180°C, time 24 hours, and obtain an amorphous NiWO4 material for standby use. The NiWO4 material of Comparative Example 2 has a similar amorphous state to that of Example 1;
[0135] (2) 100 g of commercial alumina powder was taken, 7 g of basic nickel carbonate, 22 g of molybdenum oxide, 6 g of 85% by mass phosphoric acid and 13 g of tetrabutylammonium bromide were weighed, and the mixture was heated and stirred to dissolve in deionized water. The volume was fixed according to the saturated water absorption rate of the commercial alumina powder, and the alumina powder was impregnated with the solution for 2 hours. After drying at 120° C. in an air atmosphere for 4 hours, the mixture was heated to 280° C. and low-temperature calcined for 4 hours to obtain a catalyst sample M loaded with active metals. The carbon content of the catalyst sample M was determined to be 1.52%;
[0136] (3) Weigh 12.16 g of citric acid, stir and dissolve it with deionized water, adjust the volume according to the saturated water absorption rate of sample M, and use the solution to impregnate the catalyst sample M loaded with active metal for 2 hours, with an air atmosphere pressure of 0.1 MPa, dry at 120° C. for 4 hours, switch to nitrogen, raise the temperature to 265° C., and low-temperature roast for 4 hours at a pressure of 0.15 MPa to obtain a catalyst sample containing NiMo;
[0137] (4) Take 20 g of the prepared NiWO4 material and mix it evenly with the above-mentioned NiMo catalyst sample, and prepare catalyst D2 after molding.
[0138] The evaluation conditions of the catalyst are the same as those in Example 1. The NiWO4 material analysis is shown in Table 2, the catalyst analysis and characterization results are shown in Table 3, and the evaluation result data are shown in Table 4.
[0139] Comparative Example 3
[0140] (1) Take 24g of nickel chloride hexahydrate and 33g of sodium tungstate dihydrate, dissolve them respectively with deionized water, heat the sodium tungstate solution to 60°C, add the nickel chloride solution dropwise to form a suspension solution, transfer the suspension solution to a hydrothermal kettle for hydrothermal treatment, the hydrothermal conditions are temperature 180°C, time 24 hours, and obtain an amorphous NiWO4 material for standby use. Comparative Example 3 NiWO4 material has a similar amorphous state to Example 1;
[0141] (2) 20 g of the prepared NiWO4 material and 100 g of commercial alumina powder were uniformly mechanically mixed and formed as a composite carrier;
[0142] (3) Take 120g of the above composite support, weigh 7g of basic nickel carbonate, 22g of molybdenum oxide and 6g of 85% by mass phosphoric acid, heat and stir to dissolve in deionized water, adjust the volume according to the saturated water absorption rate of the composite support, and use the solution to impregnate the composite support for 2 hours, the air atmosphere pressure is 0.1MPa, dry at 120°C for 4 hours, and then heat to 280°C and low-temperature roast for 4 hours at a pressure of 0.15MPa to obtain a catalyst sample M loaded with active metals, and its carbon content is measured to be 0.24%;
[0143] (4) Weigh 1.92 g of citric acid, stir and dissolve it with deionized water, and adjust the volume according to the saturated water absorption rate of sample M. Use the solution to impregnate the catalyst sample M loaded with active metal for 2 hours. The air atmosphere pressure is 0.1 MPa. After drying at 120°C for 4 hours, switch to nitrogen and heat to 265°C for low-temperature calcination for 4 hours at a pressure of 0.15 MPa to obtain catalyst D3.
[0144] The evaluation conditions of the catalyst are the same as those in Example 1. The NiWO4 material analysis is shown in Table 2, the catalyst analysis and characterization results are shown in Table 3, and the evaluation result data are shown in Table 4.
[0145] Comparative Example 4
[0146] (1) Take 24g of nickel chloride hexahydrate and 33g of sodium tungstate dihydrate, dissolve them respectively with deionized water, heat the sodium tungstate solution to 60°C, add the nickel chloride solution dropwise to form a suspension solution, transfer the suspension solution to a hydrothermal kettle for hydrothermal treatment, the hydrothermal conditions are temperature 180°C, time 24 hours, and obtain an amorphous NiWO4 material for standby use. The NiWO4 material of Comparative Example 4 has a similar amorphous state to that of Example 1;
[0147] (2) 20 g of the prepared NiWO4 material and 100 g of commercial alumina powder were uniformly mechanically mixed and formed as a composite carrier;
[0148] (3) Take 120 g of the above-mentioned composite carrier, weigh 7 g of basic nickel carbonate, 22 g of molybdenum oxide, 6 g of 85% by mass phosphate and 13 g of tetrabutylammonium bromide, heat and stir to dissolve in deionized water, adjust the volume according to the saturated water absorption rate of the composite carrier, and use the solution to impregnate the composite carrier for 2 hours. The air atmosphere pressure is 0.1 MPa. After drying at 120°C for 4 hours, the temperature is raised to 280°C and low-temperature roasted for 4 hours at a pressure of 0.15 MPa to obtain catalyst D4.
[0149] The evaluation conditions of the catalyst are the same as those in Example 1. The NiWO4 material analysis is shown in Table 2, the catalyst analysis and characterization results are shown in Table 3, and the evaluation result data are shown in Table 4.
[0150] Comparative Example 5
[0151] (1) 100 g of commercial alumina powder was molded as a carrier, 17 g of basic nickel carbonate, 22 g of molybdenum oxide, 16 g of ammonium metatungstate, 6 g of 85% phosphoric acid and 13 g of tetrabutylammonium bromide were weighed, heated and stirred with deionized water to dissolve, the volume was fixed according to the saturated water absorption rate of the carrier, the carrier was impregnated with the solution for 2 hours, the air atmosphere pressure was 0.1 MPa, and after drying at 120° C. for 4 hours, the temperature was raised to 280° C. and low-temperature roasted for 4 hours at a pressure of 0.15 MPa to obtain a catalyst sample M loaded with active metals, and its carbon content was measured to be 1.48%;
[0152] (2) Weigh 11.84 g of citric acid, stir and dissolve it with deionized water, and adjust the volume according to the saturated water absorption rate of sample M. Use the solution to impregnate the catalyst sample M loaded with active metal for 2 hours. The air atmosphere pressure is 0.1 MPa. After drying at 120°C for 4 hours, switch to nitrogen and heat to 265°C for low-temperature calcination for 4 hours at a pressure of 0.15 MPa to obtain catalyst D5.
[0153] The evaluation conditions of the catalyst are the same as those in Example 1. The NiWO4 material analysis is shown in Table 2, the catalyst analysis and characterization results are shown in Table 3, and the evaluation result data are shown in Table 4.
[0154] Comparative Example 6
[0155] (1) Take 24g of nickel chloride hexahydrate and 33g of sodium tungstate dihydrate, dissolve them in deionized water respectively, heat the sodium tungstate solution to 60°C, add the nickel chloride solution dropwise to form a suspension solution, transfer the suspension solution to a hydrothermal kettle for hydrothermal treatment under the conditions of 280°C for 48 hours. After the hydrothermal treatment, a NiWO4 material with obvious crystallization is obtained for standby use. The XRD spectrum is as follows Figure 2 As shown, from Figure 2 It can be seen that the NiWO4 material has typical crystal structure diffraction peaks at 30.9°, 36.5° and 54.5°, and has a good crystallization effect. It can be seen from Table 1 that the average grain size of the NiWO4 material of Comparative Example 6 is significantly increased relative to the amorphous NiWO4 material of the embodiment, and the specific surface area is reduced;
[0156] (2) Take 120g of the above composite carrier, take 20g of the prepared NiWO4 material and 100g of commercial alumina powder, mix them uniformly mechanically, and form them as a composite carrier;
[0157] (3) 7 g of basic nickel carbonate, 22 g of molybdenum oxide, 6 g of 85% phosphoric acid and 13 g of tetrabutylammonium bromide were weighed, heated and stirred to dissolve in deionized water, the volume was fixed according to the saturated water absorption rate of the composite support, the composite support was impregnated with the solution for 2 hours, the air atmosphere pressure was 0.1 MPa, dried at 120° C. for 4 hours, and then heated to 280° C. and low-temperature calcined for 4 hours at a pressure of 0.15 MPa to obtain a catalyst sample M loaded with active metals, and its carbon content was measured to be 1.55%;
[0158] (4) Weigh 12.4 g of citric acid, stir and dissolve it with deionized water, and adjust the volume according to the saturated water absorption rate of sample M. Use the solution to impregnate the catalyst sample M loaded with active metal for 2 hours. The air atmosphere pressure is 0.1 MPa. After drying at 120°C for 4 hours, switch to nitrogen and heat to 265°C for low-temperature calcination for 4 hours at a pressure of 0.15 MPa to obtain catalyst D6.
[0159] The evaluation conditions of the catalyst are the same as those in Example 1. The NiWO4 material analysis is shown in Table 2, the catalyst analysis and characterization results are shown in Table 3, and the evaluation result data are shown in Table 4.
[0160] Table 1
[0161] Analyze Project Jet fuel raw materials Sulfur content, ppm 2011 Nitrogen content, ppm 2.52 Density, g / mL 0.78558 Refractive index (20℃) 1.4401
[0162] Table 2
[0163] <![CDATA[Specific surface area / (m 2 / g)]]> Pore volume / (mL / g) Average particle size (nm) Example 1 275 0.81 3.9 Example 2 272 0.82 3.8 Example 3 271 0.83 3.7 Comparative Example 1 / / / Comparative Example 6 182 0.58 28.2
[0164] Table 3
[0165]
[0166]
[0167] It can be seen from the above table that the composite carrier prepared by the amorphous NiWO4 material provided by the present invention has a larger specific surface area and pore volume, which is conducive to the subsequent hydrodesulfurization reaction. 4+ ) / n(Mo Total ) and n(W 4+ ) / n(W Total ) ratio, the easier it is for the active metals Mo and W in the catalyst to be sulfided, the higher the utilization rate of the active metals, and the better the hydrogenation activity of the catalyst.
[0168] Table 4
[0169]
[0170]
[0171] It can be seen from the above table that the hydrogenation catalyst prepared by the method of the present invention has higher hydrodesulfurization activity under the same evaluation conditions.
[0172] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a hydrogenation catalyst, characterized in that: The method comprises the following steps: (1) impregnating a support with a solution containing an active metal and a quaternary ammonium salt compound, and then performing a first calcination to obtain a calcined product; the active metal is selected from at least one of the metals of Group VIII and / or at least one of the metals of Group VIB, and the support comprises an amorphous NiWO4 material and an inorganic heat-resistant matrix; (2) post-treating the calcined product of step (1) with an organic compound, and then performing a second calcination to obtain a hydrogenation catalyst, wherein the organic compound is selected from at least one of an alcohol compound, a carboxylic acid compound and an organic amine compound.
2. The method according to claim 1, wherein: In step (1), the active metal is selected from Ni and / or Mo, preferably Ni and Mo; Preferably, the active metal is provided by a precursor of each active metal, further preferably provided by a soluble compound selected from each active metal, further preferably selected from at least one of nickel nitrate, nickel chloride, basic nickel carbonate and nickel sulfate, and at least one of ammonium molybdate, sodium molybdate and molybdenum oxide; Preferably, the amount of the active metal precursor is such that the prepared hydrogenation catalyst has a Ni content of 0.1-10 wt % as oxide and a Mo content of 5-30 wt % as oxide; Preferably, the mass ratio of the precursor of the active metal Ni to the amorphous NiWO4 material is 1:3-1:30, calculated as oxide.
3. The method according to claim 2, wherein: In step (1), the quaternary ammonium salt compound is selected from C4-C20 quaternary ammonium salt compounds, preferably selected from at least one of tetramethylammonium bromide, tetraethylammonium bromide, tetrapropylammonium bromide, tetrabutylammonium bromide, dodecyltrimethylammonium bromide and hexadecyltrimethylammonium bromide, and more preferably selected from at least one of tetrabutylammonium bromide, dodecyltrimethylammonium bromide and hexadecyltrimethylammonium bromide; Preferably, in step (1), the molar ratio of the quaternary ammonium salt compound to the active metal Ni in terms of element is 0.3:1-3:1, more preferably 0.5:1-2:
1.
4. The method according to any one of claims 1 to 3, wherein: In step (1), the average grain size of the amorphous NiWO4 material is 2-5 nm; Preferably, in step (1), the amorphous NiWO4 material is prepared by the following method: preparing a NiWO4 precursor by a solid phase reaction method and / or a precipitation method, and then subjecting the precursor to a hydrothermal treatment to obtain an amorphous NiWO4 material, wherein the conditions of the hydrothermal treatment include: a temperature of 120-240°C and a time of 2-48h; Preferably, the conditions of the hydrothermal treatment include: temperature of 140-220°C and time of 12-36h; Preferably, the NiWO4 precursor is prepared by a precipitation method using a Ni metal precursor and a W metal precursor; Preferably, the Ni metal precursor is a soluble compound of Ni, and is further preferably selected from at least one of nickel nitrate, nickel chloride, basic nickel carbonate and nickel sulfate; Preferably, the W metal precursor is a soluble compound of W, and is further preferably selected from at least one of ammonium metatungstate, sodium tungstate and ammonium tungstate; Preferably, the molar ratio of the Ni-containing metal precursor to the W-containing metal precursor is 1:5-5:1, calculated on an element basis.
5. The method according to any one of claims 1 to 4, wherein: The inorganic heat-resistant matrix is selected from at least one of aluminum oxide, zirconium oxide, titanium oxide and silicon oxide, preferably aluminum oxide; Preferably, the mass ratio of the amorphous NiWO4 material to the inorganic heat-resistant matrix is 1:2-1:
20.
6. The method according to any one of claims 1 to 5, wherein: In step (1), based on the total amount of the calcined product, the carbon content in the calcined product is 0.5-2.5% by weight, preferably 0.8-2% by weight; Preferably, in step (1), the first calcination conditions include: temperature of 180-350° C., time of 1-8 h; Further preferably, in step (1), the conditions of the first calcination include: temperature of 230-300° C. and time of 2-6 h.
7. The method according to any one of claims 1 to 6, wherein: In step (2), the alcohol compound is selected from at least one of ethylene glycol, propylene glycol, diethylene glycol and butanediol; Preferably, in step (2), the carboxylic acid compound is at least one selected from citric acid, acetic acid, oxalic acid, aminotriacetic acid, 1,2-cyclohexanediaminetetraacetic acid, aminotriacetic acid, malic acid and maleic acid; Preferably, in step (2), the organic amine compound is ethylenediamine and / or ethylenediaminetetraacetic acid.
8. The method according to any one of claims 1 to 7, wherein: In step (2), the post-treatment comprises: using an impregnation method to impregnate the calcined product of step (1) with a solution containing at least one of an alcohol compound, a carboxylic acid compound and an organic amine compound; Preferably, the mass ratio of the organic compound in step (2) to the carbon in the calcined product in step (1) is 1:1-10:1, more preferably 2:1-8:1; Preferably, in step (2), the conditions of the second calcination include: temperature of 180-350° C., time of 1-8 h; Further preferably, in step (2), the conditions of the second calcination include: temperature of 200-280° C., time of 2-6 h; Preferably, in step (2), the second calcination is performed under an inert atmosphere, and preferably the inert atmosphere is selected from at least one of nitrogen, helium and argon.
9. A hydrogenation catalyst prepared by the method according to any one of claims 1 to 8.
10. Use of the hydrogenation catalyst according to claim 9 in the hydrogenation reaction of aviation kerosene raw materials; Preferably, the conditions of the hydrogenation reaction include: The reaction temperature is 230-300℃, the reaction pressure is 1-4MPa, and the volume space velocity is 2-6h -1 , the volume ratio of hydrogen to oil is 50:1-200:1.
Citation Information
Patent Citations
Heavy oil hydrogenation catalyst and preparation method thereof, and heavy oil hydrogenation treatment method
CN108421561A
Hydroprocessing bulk catalyst and uses thereof
US20100234212A1
Hydroprocessing catalysts and their production
US20140374319A1